Simulation of IoT Smart Home Network with Decision Making Based on MajorDoMo Platform - U. A. Vishniakou; ChuYue Yu (Цифровая трансформация)
The purpose of the article is to model a smart home with decision-making and the use of the MajorDoMo IoT platform instead of a cloud platform. The main features of the article are: modeling of the IoT network for controlling the control unit on the MajorDoMo platform, the use of the MajorDoMo IoT platform in the Windows system for making decisions when controlling household appliances (fan or air conditioner) based on the temperature and humidity values received from a smartphone modeling sensors, transmitting the results of controlled data to the user's home page. The structure of the MajorDoMo platform is given, its functions are described, and commands for decision support are considered. The use of product rules is proposed as a decision-making model. An example of such a description for data regulation by the household appliances is given. The user can log into the IoT network and view changes in temperature and humidity in real time, as well as check the regulation of the equipment. The possibilities of the PHP language for the implementation of the control process are presented, in which the household device begins to adjust the parameters when the environmental monitoring system detects that the corresponding data exceeds the set threshold.